2005
DOI: 10.1038/ng1524
|View full text |Cite
|
Sign up to set email alerts
|

Positional identification of TNFSF4, encoding OX40 ligand, as a gene that influences atherosclerosis susceptibility

Abstract: Ath1 is a quantitative trait locus on mouse chromosome 1 that renders C57BL/6 mice susceptible and C3H/He mice resistant to diet-induced atherosclerosis. The quantitative trait locus region encompasses 11 known genes, including Tnfsf4 (also called Ox40l or Cd134l), which encodes OX40 ligand. Here we report that mice with targeted mutations of Tnfsf4 had significantly (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
240
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(253 citation statements)
references
References 42 publications
10
240
3
Order By: Relevance
“…Emerging evidence supports a role of OX40-OX40L in atherosclerosis [21]. Furthermore, in the present study, OX40L was found to be up-regulated in PBMCs from children and young adults with FH.…”
Section: Regulation Of Mmp-9 By Ox40 Ox40l and Oxldl In Thp-1 Monocytessupporting
confidence: 87%
See 2 more Smart Citations
“…Emerging evidence supports a role of OX40-OX40L in atherosclerosis [21]. Furthermore, in the present study, OX40L was found to be up-regulated in PBMCs from children and young adults with FH.…”
Section: Regulation Of Mmp-9 By Ox40 Ox40l and Oxldl In Thp-1 Monocytessupporting
confidence: 87%
“…The gene encoding OX40L has been found to influence the development of atherosclerosis in both mice and humans [21]; in the present study we have shown that PBMCs from children and young adults with FH have enhanced expression of OX40L compared with those from matched healthy controls. Moreover, OX40, acting through OX40L, enhanced the oxLDL-induced expression of MMP-9 in THP-1 monocytes.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…For example, evidence from QTL mapping and analyses of knockouts implicates Tnfsf4 in diet-induced atherosclerosis in mice (Wang et al 2005b); however, genetic association studies have not provided consistent evidence for its involvement in humans (Koch et al 2008). Similar difficulties are found for the involvement of type II SH2 domain-containing inositol 5-phosphatase in the metabolic syndrome (Kaisaki et al 2004;Marcano et al 2007) and regulators of G protein signaling in anxiety (Fullerton et al 2008).…”
Section: How Much Does Genetic Architecture Vary Between Phenotypes?mentioning
confidence: 99%
“…3 Several large-scale association studies using a large number of genetic variations, including single nucleotide polymorphisms (SNPs), have recently identified the susceptibility genes and loci for CAD. [4][5][6][7][8][9][10][11][12] However, not all of the reported associations could be replicated in other studies even if middle-to large-sized samples were investigated in the original reports, suggesting that the contribution of genetic factors was not large enough to be replicated in some cases. 13 Validation studies for the association in other populations are, therefore, crucial to establish the role of diseaserelated genes.…”
Section: Introductionmentioning
confidence: 99%